Adverse influence of multilevel socioeconomic status on physical activity: results from a national survey in Vietnam - Thi Hoang Lan Vu; Thi Tu Quyen Bui; Thi Kim Ngan Nguyen; Van Minh Hoang (BMC, 2020)
Abstract Background This study aims to explore associations of individual- and provincial-level socioeconomic status (SES) and the combined interaction among these SES with individual physical activity (PA). Method This analyze used data of 3068 Vietnamese people aged 18-65 years from the national representative STEPS survey in 2015 (STEPS2015). The survey collected PA-related data using the Global PA Questionnaire Version 2 and those on provicial-level characteristics from two surveys in 2014, namely the Intercensal Population and Housing Survey (IPHS) and The Vietnam Household Living Standard Survey (VLSS2014). Multilevel linear analyze was performed with individual and provincial characteristics as independent variables and the metabolic equivalent (MET) score - the indicator of individual PA - as the dependent variable. Results Male and female participants with insufficient PA accounted for 20.2 and 35.7%, respectively. Both individual- and provicial-level SES were inversely associated with the individual PA level. As the provincial-level monthly income increased by 1 million Vietnam Dongs, the total PA score of individuals residing in that province reduced by 1900 METS. A buffering effect was reported between provincial and individual SES, as the provincial average income increased, the differences in PA scores between different SES groups decreased. Conclusion Our data suggest that Vietnamese individuals in low SES groups tended to be more physically active than those in high SES groups because their PA was largely related to work.